Article Review: The Phenomenon of Cytokine Storm - Aldoori, Zina A. A.; Hameed, Nagham I. Abdul (Journal for Research in Applied Sciences and Biotechnology, 2022)
Cytokine storms are much more common these days because of the corona epidemic. Cytokine storm is a serious complication known as an infusion reaction seen in the presence of infection or drug side effects. The reason for this is the increase in the number of white blood cells to fight viral and bacterial infections, as a result of which more cytokines are secreted and the feedback provided by them causes a severe inflammatory reaction and death if the patient does not focus on it. This article describes the concept of the Cytokine storm, how to increase cytokine and create a Cytokine storm, types of Cytokine storms, factors involved in its creation, and methods of diagnosis and treatment.